Bargaining Power of Multinationals and Host Governments - Fagre, Nathan; Wells, Louis T. (Journal of International Business Studies, 1982)
One of the outcomes of negotiation between multinationals and host governments in developing countries—the extent of foreign ownership of subsidiaries—is influenced by the bargaining power of the two parties. Foreign ownership, measured in various ways, appears to be affected by the level of technology of the multinational, the degree to which a multinational attempts to differentiate its products, the extent to which a subsidiary's output is exported to other parts of the multinational, the diversity of products offered by the multinational, and the extent of competition by other multinationals. The relationship between some of these variables and ownership is not a simple one. One variable that others have mentioned as probably affecting bargaining power—size of the investment in question—appears not to play a significant role in government policies toward ownership, but many large projects tend to be located in countries that have lenient ownership policies.